Teaching Writing through Canva Application - Muhamad Sofian Hadi; Lidiyatul Izzah; Qondila Paulia (Journal of Languages and Language Teaching, 2021)
This study aims to investigate the effectiveness of using Canva application media to enhance students’ writing skills. This research was conducted in July-August at Mts Al-Islamiyah, Ciledug. Researchers used a quantitative method which is pre-experimental research design by applying pre-test and post-test. Writing tests were employed in collecting students’ achievement as instruments of this study. Researchers used one class in class IX-1 MTs Al-Islamiyah Ciledug as research samples. Determining samples of this study used the random sampling technique. To analyze the research data, researcher applied t-test. Based on the research analysis, the mean score of students’ writing test on the post-test was 70.83, and the pre-test was 64.73. The results also showed that the T-cal value (9,585) was higher than the Ttable (2.021), at the 5% significance level. If the result t-test was higher than t-table. It indicated that the alternative hypothesis (Ha) was accepted, and (H0) was rejected. Based on the results of the t-test calculation, this current study can be concluded that the Canva Application is an effective media to facilitate students to improve their writing performance. For further studies, English teachers can imitate the basic theory of this study as consideration to teach writing skills.